MIL-53(Al) and NH2-MIL-53(Al) modified α-alumina membranes for efficient adsorption of dyes from organic solvents. Issue 28 (19th March 2019) - Amirilargani, Mohammad; Merlet, Renaud B.; Hedayati, Pegah; Nijmeijer, Arian; Winnubst, Louis; de Smet, Louis C. P. M.; Sudhölter, Ernst J. R.
Abstract : MIL-53(Al) and NH2 -MIL-53(Al) modified α-alumina membranes are investigated for the adsoption of organic dyes from organic solvents. Abstract : To the best of our knowledge, for the first time MIL-53(Al) and NH2 -MIL-53(Al) modified α-alumina membranes are investigated for the adsorption of organic dyes from organic solvents. These new, modified membranes show excellent adsorption of high concentrations of Rose Bengal dye in methanol and isopropanol solutions.